Textbook of economic analysis - Nevin, Edward (Basingstoke : Macmillan, 1981)
This book is designed to 'provide an introduction to the groundwork on contemporary economic and monetary theory'. It is a good basic textbook, suitable mainly for the University student who is embarking on a course in Economics.
Includes bibliographical references and index.
aia 11/10/2017
Loans
Keywords: Economics; Economics -- Theories